Pengaruh Modernisasi Sistem Administrasi Perpajakan Dan Penerapan Good Corporate Governance Terhadap Penghindaran Pajak Ilegal - Lia Syafitri, Novika; Rizal, Syamsu (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Most of the tax revenue is used as the mainstay of state revenue from corporations large. The large number of Bandar Lampung corporations is likely to increase tax revenues, but unfortunately there are common ground corporations to do tax evasion illegally. The survey is aimed at analyzing and showing reality due to the modernization of the tax administration system and the implementation of GCG on illegal tax avoidance. examination was carried out at the KPP Bandar Lampung 1. The use of the subject of investigation it means taxpayers registered with KPP Bandar Lampung 1. The survey used a quantitative method, the technique of collecting data in the survey was in the form of distributing surveys via google form. Determination of the sample in the survey using purposive sample and includes 30 issuers. Hypothesis testing technique is done using t and f. Statistical analysis that used is SPSS V17. The result of the survey shows that the modernization of the tax administration system has a positive impact on sig. 0.043 and has a positive impact on the regression coefficient of 0.737. The implementation of GCG is positively affected and is significant with sig. 0.032, and positively affected by a regression coefficient of 0.627. Simultaneously 2 variables have an impact on illegal tax evasion in taxpayers registered with KPP Pratama Bandar Lampung 1.